2021
DOI: 10.1002/jcsm.12788
|View full text |Cite
|
Sign up to set email alerts
|

Human gut microbiome impacts skeletal muscle mass via gut microbial synthesis of the short‐chain fatty acid butyrate among healthy menopausal women

Abstract: Background Increasing evidence suggests that human gut microbiome plays an important role in variation of skeletal muscle mass (SMM). However, specific causal mechanistic relationship of human gut microbiome with SMM remains largely unresolved. Understanding the causal mechanistic relationship may provide a basis for novel interventions for loss of SMM. This study investigated whether human gut microbiome has a causal effect on SMM among Chinese community-dwelling healthy menopausal women. Methods Estimated SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 46 publications
2
50
0
Order By: Relevance
“…A mice model investigating the effect of chronic butyrate administration in aging mice supports above reported effects as butyrate‐reduced intramuscular fat accumulation and increased markers of mitochondrial biogenesis, antioxidant activity, and oxidative metabolism in the skeletal muscle 252 . A human cross‐sectional study using mendelian randomization analysis has identified a causal relationship between the production of microbial butyrate and appendicular lean mass in Chinese menopausal women, suggesting that butyrate may play a role in maintaining muscle mass in humans as well 253 …”
Section: Mechanistic Underpinning: Butyrate and Interorgan Crosstalksupporting
confidence: 53%
“…A mice model investigating the effect of chronic butyrate administration in aging mice supports above reported effects as butyrate‐reduced intramuscular fat accumulation and increased markers of mitochondrial biogenesis, antioxidant activity, and oxidative metabolism in the skeletal muscle 252 . A human cross‐sectional study using mendelian randomization analysis has identified a causal relationship between the production of microbial butyrate and appendicular lean mass in Chinese menopausal women, suggesting that butyrate may play a role in maintaining muscle mass in humans as well 253 …”
Section: Mechanistic Underpinning: Butyrate and Interorgan Crosstalksupporting
confidence: 53%
“…To ensure data robustness and the accuracy of results, the SNPs were quality checked to obtain compliant IVs: (1) SNPs associated with GM taxa reached genome-wide significance threshold ( P <5×10 -8 ). Since the number of eligible IVs ( P <5×10 -8 ) was extremely small, a relatively more comprehensive threshold ( P <1×10 -5 ) ( 20 , 21 ) was selected to obtain a more comprehensive result. (2) To meet the MR assumptions, we performed a linkage disequilibrium (LD) analysis (R 2 <0.001, clumping distance = 10,000kb) based on European-based 1,000 Genome Projects and removed the SNPs that did not meet the requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Isobutyrate is a kind of short-chain fatty acid. Studies have confirmed that the increase in butyrate synthesis by intestinal microbes is closely related to the increase in skeletal muscle index [ 39 ]. Fatty acids, glucose, and lactic acid can be metabolized into pyruvate, which is transported to the mitochondria by the mitochondrial pyruvate carrier (MPC) for the citric acid cycle [ 40 ].…”
Section: Discussionmentioning
confidence: 99%